2012
DOI: 10.1530/eje-11-0838
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Primary HT and risk for breast cancer: a systematic review and meta-analysis

Abstract: Objective: The association between hypothyroidism and breast cancer has been described from very early on. Breast and thyroid tissue are interconnected on a molecular level mainly through activation of thyroid hormone receptors expressed on cells of the mammary gland as well as on the plasma membrane of breast cancer cells. Despite the experimental evidence the true value of hypothyroidism as a risk factor for breast cancer remains controversial. Methods: We searched the PubMed database through February 2011 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
2
47
1
2
Order By: Relevance
“…Clinical hypothyroidism seems to be a risk factor for several neoplasias such as liver cancer, thyroid malignancies, high-grade glioblastomas and human breast cancer (Reddi et al 2007, Polyzos et al 2008, Hassan et al 2009, Angelousi et al 2012. In contrast, increased TH levels have been associated with higher risk of esophageal, thyroid, breast and ovarian cancer development (Turkyilmaz et al 2005, Rasool et al 2014, Kunjumohamed et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical hypothyroidism seems to be a risk factor for several neoplasias such as liver cancer, thyroid malignancies, high-grade glioblastomas and human breast cancer (Reddi et al 2007, Polyzos et al 2008, Hassan et al 2009, Angelousi et al 2012. In contrast, increased TH levels have been associated with higher risk of esophageal, thyroid, breast and ovarian cancer development (Turkyilmaz et al 2005, Rasool et al 2014, Kunjumohamed et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Shering et al (18) and Ito and Maruchi (17) observed that Japanese women with Hashimoto's thyroiditis had a higher incidence of mammary cancer than women without thyroid disease. Two recent meta-analyses showed no significant association, except for autoimmune thyroiditis which increased breast cancer risk; however, the heterogeneity of the studies analyzed precludes firm conclusions (7,22).…”
Section: Discussionmentioning
confidence: 94%
“…However, there is controversy concerning the relationship between thyroid disorders and breast cancer incidence (7). Thyroid hormones (THs) could participate directly on mammary carcinogenesis, or indirectly through their action in changes in the patterns of secretion of other hormones such as E, Pg, PRL and/or GH, among others.…”
Section: Introductionmentioning
confidence: 99%
“…T3 can influence the mammary gland; this involves the activation of TR present in the mammary gland inducing differentiation and lobular growth in an estrogenlike manner. However, there is controversy regarding the relationship between thyroid disorders and breast cancer (BC) incidence [19] . In this chapter, the influence of T3 on BC will be reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…An inhibitory effect of iodine on BC was suggested to be attributable to its antioxidant role [60][61][62] ; however, some in vitro experiments have shown a proliferative effect of triiodothyronine on BC cell lines [63,64] . A recently conducted meta-analysis found no statistically significant association between TH replacement and BC risk [19] . One of these studies demonstrated primary hyperthyroidism as a strong protective factor against BC after adjusting for clinical parameters including TH replacement therapy [47] .…”
mentioning
confidence: 97%